1994
DOI: 10.2190/5hxy-acm5-q6pk-04h5
|View full text |Cite
|
Sign up to set email alerts
|

ECT in the Treatment of Patients with Neurological and Somatic Disease

Abstract: ECT is safe and effective for the treatment of affective and catatonic disorders in patients with most neurological and medical diseases, including elderly and debilitated patients with multiple illnesses, if the specific medical risks are carefully evaluated in each case, and appropriate modifications of technique are used to reduce the risk of potential complications. Apart from its use in psychiatry, ECT has been reported to have therapeutic effects in Parkinson's disease, neuroleptic malignant syndrome, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…20 In our patient, after a failure to respond to these initial approaches, it was felt that to continue pursuing additional medical therapies would place him at an unacceptable risk of developing serious complications of malignant syndrome, including rhabdomyolysis, acute renal failure, disseminated intravascular coagulation and deep vein thrombosis. Given that ECT has been shown to be a safe and effective treatment in the medically ill, 8 in patients with PD 9 and in NMS, 10 we felt that ECT was the most appropriate treatment. In fact, Trollor and Sachdev 10 have argued that the response to ECT appears to be faster than to pharmacological treatment, although no direct comparison studies have been performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In our patient, after a failure to respond to these initial approaches, it was felt that to continue pursuing additional medical therapies would place him at an unacceptable risk of developing serious complications of malignant syndrome, including rhabdomyolysis, acute renal failure, disseminated intravascular coagulation and deep vein thrombosis. Given that ECT has been shown to be a safe and effective treatment in the medically ill, 8 in patients with PD 9 and in NMS, 10 we felt that ECT was the most appropriate treatment. In fact, Trollor and Sachdev 10 have argued that the response to ECT appears to be faster than to pharmacological treatment, although no direct comparison studies have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…7 Electroconvulsive therapy (ECT) is recognised to be a safe and effective treatment for a range of affective and catatonic disorders in patients with neurological disorders. 8 Case reports have also indicated that ECT has therapeutic effects in patients with severe PD but without affective or psychotic disorders. 9 Multiple case reports have demonstrated the effectiveness of ECT in the treatment of NMS.…”
Section: Introductionmentioning
confidence: 99%
“…Relaxation therapy, guided imagery, systematic desensitisation, problem solving, education and other supportive interventions (Level I) 15,16 Depressive symptoms Relaxation therapy, guided imagery, psycho-education, problem solving, and other supportive interventions (Level I) 15,16,[603][604][605] Note: Specialised interventions that can be conducted by appropriately qualified health professionals are outlined in Chapter 4.…”
Section: Anxietymentioning
confidence: 99%
“…ECT has demonstrated efficacy in the treatment of severe depression, and is generally well-tolerated even in those with concurrent medical conditions (Level I). [603][604][605]683 • Psychostimulants: Patients with advanced cancer may experience some improvement in depressed mood,appetite and well-being when treated with low-dose psychostimulants. 698 They are generally well-tolerated, and a particular benefit in terminally-ill patients is the rapid onset of action.…”
mentioning
confidence: 99%
“…While therapeutic strategies against catatonia are proven to be successful in schizophrenic disorders less is known about their effect in catatonic syndromes caused by somatic disorders as in the following case (Tandon et al 1988;Zwil and Pelchat 1994).…”
Section: Introductionmentioning
confidence: 99%